Implementation of the IDEFICS intervention across European countries: perceptions of parents and relationship with BMI. (December 2015) - De Bourdeaudhuij, I.; Verbestel, V.; De Henauw, S.; Maes, L.; Mårild, S.; Moreno, L. A.; Barba, G.; Siani, A.; Kovács, E.; Konstabel, K.; Tornaritis, M.; Pigeot, I.; et al.
Summary: Objectives: The primary aim of the present study was to obtain insight into parents' perception of the IDEFICS intervention at the school or preschool/kindergarten and community levels and whether they received specific materials related to the intervention. The secondary aim was to analyse whether parents who reported higher levels of exposure to the IDEFICS intervention had children with more favourable changes in body mass index (BMI) z ‐scores between baseline and after 2 years of intervention. Methods: Process evaluation of the IDEFICS intervention investigated the implementation of the 2‐year intervention in the intervention communities. Intervention group parents ( n  = 4, 180) in seven countries (Belgium, Cyprus, Estonia, Germany, Italy, Spain and Sweden) answered questions about their exposure to the IDEFICS study. To analyse the relationship between exposure and BMI z ‐score, a composite score was calculated for exposure at the setting and at the community levels. Results: The frequency of parental exposure to the IDEFICS messages not only through the community but also through the (pre)school/kindergarten was lower than what was intended and planned. The dose received by the parents was considerably higher through the (pre)school/kindergarten settings than that through the community in all countries. Efforts by the settings or communities related to fruit and vegetable consumption (range 69% to 97%), physical activity promotion (range 67% to 91%) and drinking water (range 49% to 93%) were more visible and also realized more parental involvement than those related to TV viewing, sleep duration and spending time with the family (below 50%). Results showed no relation of parental exposure at the setting or the community level on more favourable changes in children's BMI z ‐scores for the total sample. Country‐specific analyses for parental exposure at the setting level showed an expected positive effect in German girls and an unexpected negative effect in Italian boys. Conclusion: Parental exposure and involvement in the IDEFICS intervention in all countries was much less than aimed for, which might be due to the diverse focus (six key messages) and high intensity and duration of the intervention. It may also be that the human resources invested in the implementation and maintenance of intervention activities by the study centres, the caretakers and the community stakeholders were not sufficient. Higher levels of parental exposure were not related to more favourable changes in BMI z ‐scores. © 2015 World Obesity